L’essor musical de la basilique de San Petronio au XVe siècle : I-Bsp, Fragments A, B, C, D, E, une relecture - Johan Guiton (Artes)
The musical chapel of the Basilica of San Petronio in Bologna boasts six centuries of nearly continuous activity. In relation to the fifteenth century, however, the precious repertoire of the Archivio musicale contains only five fragments of polyphonic music (I-Bsp, Fragments A, B, C, D, E). Discovered by Sergio Paganelli in 1967 and catalogued by Charles Hamm the following year, they constitute the only surviving example of canto figurato dating back to the earliest decades of the institution’s history, from the formation of the schola clericorum by Eugene IV in 1436 until the period when Giovanni Spataro began his tenure as maestro di canto (1512). Taking as its point of departure a methodical transcription of these incomplete folios, this paper analyses the mensural notation, borrowed material, and compositional techniques contained in the five pieces (four masses and a Magnificat). While the music is in keeping with the theoretical concerns of the second half of the fifteenth century, some striking singularities pave the way for liturgical and prosopographical scrutiny related to the Petronian institution and provide new insights into the possible restitution of the lost voices.